Study of demography risk factors of simple and complex febrile seizure and associated infection in children at tertiary care center - Pant, Dikshya; Nepal, Archana; Prajapati, Alisha; Shrestha, Shova; Pokhrel, Bhisma (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Febrile seizures are seizures that occur in children between 6 to 60 months with a temperature of 38°C or higher. It commonly affects male with a peak incidence in below 2 years old. This study aims at identifying the demographic profile of children admitted with the diagnosis of febrile seizure in order to anticipate the condition and counsel the parents.Method: This is a retrospective cross sectional study conducted in the pediatric ward of Patan Hospital. Medical records of the patients admitted with a diagnosis of febrile seizure (simple or complex) in pediatric ward of Patan Hospital between January 2016 to 2019 were reviewed and data mentioned in the proforma were collected. Ethical approval was taken from the Institutional Review Committee of Patan Academy of Health Sciences (IRC-PAHS). The data was analyzed using Statistical Packages for Social Sciences Version 25 and frequency and proportion was calculated.Result: Out of 277 cases fulfilling the study criteria, 70.4% had simple febrile seizure whereas 29.6% had complex febrile seizure. The mean age of the patients was 23.13 months ±12.8 and the median was 19 months (IQR: 14-29). Around 58.12% were males and 41.88% females. Viral fever accounted for the maximum number of infections in around 22.3% (62/277) of patients and viral URTI in 20.21% (56/277).Conclusion: The study adds to the existing knowledge of febrile seizure in order to help the clinician anticipate febrile seizure.